2023
DOI: 10.3233/wor-220428
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of impaired functioning among long COVID patients

Abstract: BACKGROUND: There is limited information on what acute factors predict more long-term symptoms from COVID-19. OBJECTIVE: Our objective was to conduct an exploratory factor analysis of self-reported symptoms at two time points of Long COVID-19. METHODS: Data from patients with Long COVID-19 were collected at the initial two weeks of contracting SARS CoV-2 and the most recent two weeks, with a mean duration of 21.7 weeks between the two-time points. At time point 2, participants also complete the Coronavirus Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The human gut microbiota is a powerful modulator of host immune responses and metabolism, and there is increasing evidence that chronic low-grade inflammation plays a significant role in the pathogenesis of chronic inflammatory-related diseases. Jason et al [19] found that both before and at the onset of mononucleosis among college students, gastrointestinal symptoms were predictive of severe cases of ME/CFS six months after infection. Similarly, Jason and Dorri [20] found that gastrointestinal symptoms during the first few weeks of Coronavirus disease 2019 (COVID-19) were predictors of more serious consequences of COVID-19 about 6 months later.…”
Section: Resultsmentioning
confidence: 99%
“…The human gut microbiota is a powerful modulator of host immune responses and metabolism, and there is increasing evidence that chronic low-grade inflammation plays a significant role in the pathogenesis of chronic inflammatory-related diseases. Jason et al [19] found that both before and at the onset of mononucleosis among college students, gastrointestinal symptoms were predictive of severe cases of ME/CFS six months after infection. Similarly, Jason and Dorri [20] found that gastrointestinal symptoms during the first few weeks of Coronavirus disease 2019 (COVID-19) were predictors of more serious consequences of COVID-19 about 6 months later.…”
Section: Resultsmentioning
confidence: 99%